Daya Tarik dan Eksistensi Komunikasi Dinas Komunikasi dan Informatika Provinsi Jawa Barat Dalam Pencegahan Penyebaran Berita Hoaka - Dewi, Rahma; Kurniati, Poni Sukaesih (Jurnal Common, 2020)
The spread of Hoaks news became a continuous problem in the province of West Java because it is still a large number of hoaks. The purpose of this journal is to determine the attractiveness and existence of communication of the Department of Communications and Informatics of West Java province in preventing the spread of hoaks. The method used in the manufacture of this journal is a descriptive method with a qualitative approach. The result of this research is the Department of Communication and Informatics of West Java province in the appeal and existence of communication has not been maximized so that it has not been able to suppress the spread of Hoaks news in West Java However, with the strategy that is used more prioritize online media considering that the modern society can be a supporting to suppress the spread of hoaks news even eliminated Hoaks news in West Java province